The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
1985
DOI: 10.1029/gl012i008p00487
|View full text |Cite
|
Sign up to set email alerts
|

Equatorial airglow depletions induced by thermospheric winds

Abstract: Interferometric observations of the 630.0 nm nightglow brightness at the equatorial station of Arequipa, Peru [16.2°S, 71.4°W geographic, 3.2°S dip latitude] have revealed widespread areas of airglow depletion, with reductions in intensity as large as factors of 3 or 4. These depletions correlated closely with large increases of the equatorward (northward) wind and the 630.0 nm kinetic temperature. On occasion, the usually small meridional wind reached a velocity of 100 m/s near 22h LT lasting for 1 to 2 hours… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
12
0

Year Published

1986
1986
2004
2004

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(13 citation statements)
references
References 18 publications
1
12
0
Order By: Relevance
“…The explanation of these features, in terms of a meridional circulation cell with accompanying adiabatic heating and cooling (Raghavarao et al, 1993), is called into question by the`coupled model' calculations of Fuller-Rowell et al (1997), who invoke instead chemical heating from the recombination of O + ions. The wind explanation seems to be supported by the observations of Meriwether et al (1985), who observed depletions of the red k6300 airglow around 22 LT at Arequipa, Peru (16°S, just south of the dip equator), which they attributed to the plasma lifting produced by the equatorward winds associated with the meridional anomaly (see Eq. 6) .…”
Section: The Equatorial`trough' In the Neutral Thermospheresupporting
confidence: 63%
“…The explanation of these features, in terms of a meridional circulation cell with accompanying adiabatic heating and cooling (Raghavarao et al, 1993), is called into question by the`coupled model' calculations of Fuller-Rowell et al (1997), who invoke instead chemical heating from the recombination of O + ions. The wind explanation seems to be supported by the observations of Meriwether et al (1985), who observed depletions of the red k6300 airglow around 22 LT at Arequipa, Peru (16°S, just south of the dip equator), which they attributed to the plasma lifting produced by the equatorward winds associated with the meridional anomaly (see Eq. 6) .…”
Section: The Equatorial`trough' In the Neutral Thermospheresupporting
confidence: 63%
“…The observed behaviors of the nighttime equatorial thermospheric neutral winds and temperatures have been described in several papers Meriwether et al, 1985Meriwether et al, , 1986Biondi et al, 1990Biondi et al, , 1991 100 mm aperture Arequipa instrument and the 150 mm aperture Arecibo instrument have comparable sensitivities and have been described in a number of publications [e.g., Burnside et al, 1981;Biondi and Siplet, 1985;Biondi and Meriwether, 1985;Meriwether et al, 1997]. The measured Doppler shifts in the 630 nm nightglow OI line for observations along several azimuths at 600 zenith angle and in the zenith have been used to determine the corresponding line-of-sight (los) velocities.…”
Section: Introductionmentioning
confidence: 99%
“…In the terrestrial environment, this emission of O I generally has two causes; either excitation by impact of energetic electrons produced by solar Extreme-ultraviolet (EUV) photoionization or ionization through precipitation of auroral particles, or by radiative recombination of ionospheric O + . The later reaction is also responsible for the 630.0 and 777.4 nm emissions often observed by ground-based observers at equatorial or mid-latitude stations (Weber et al, 1978;Meriwether et al, 1985;Makela et al, 2001). …”
Section: Instrumentation: Image/fuv Si-13mentioning
confidence: 99%